1995
DOI: 10.7326/0003-4819-123-10-199511150-00001
|View full text |Cite
|
Sign up to set email alerts
|

The “Battering Syndrome”: Prevalence and Clinical Characteristics of Domestic Violence in Primary Care Internal Medicine Practices

Abstract: In a large, diverse, community-based population of primary care patients, 1 of every 20 women had experienced domestic violence in the previous year; 1 of every 5 had experienced violence in their adult life; and 1 of every 3 had experienced violence as either a child or an adult. Current domestic violence is associated with single or separated status, socioeconomic status, substance abuse, specific psychological symptoms, specific physical symptoms, and the total number of physical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
367
6
40

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 656 publications
(446 citation statements)
references
References 0 publications
33
367
6
40
Order By: Relevance
“…Studies show that episodes of violence tend to repeat themselves and become progressively worse 29,30 . They also show more intense use of ambulatory and hospital services, thus constituting a significant clientele 31,32 . Furthermore, repeat violence and deaths due to violence among women previously filing reports show the frailty of the network of care and protection for women in a situation of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that episodes of violence tend to repeat themselves and become progressively worse 29,30 . They also show more intense use of ambulatory and hospital services, thus constituting a significant clientele 31,32 . Furthermore, repeat violence and deaths due to violence among women previously filing reports show the frailty of the network of care and protection for women in a situation of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based and clinical studies have consistently found acute and long-term mental and physical health problems in women who have experienced IPV: e.g., lower self-rated health status, higher symptom levels; increased physical limitations, chronic pain, decreased productivity, and increased health services use Campbell & Soeken, 1999;Coker, Smith, McKeown, & King, 2000;Collins et al, 1999;Golding, 1999;McCauley et al, 1995;Sutherland et al, 2001). The mental health consequences of IPV, particularly PTSD and posttraumatic stress symptoms, have also been documented extensively.…”
Section: Ipv and Health Statusmentioning
confidence: 99%
“…Conversely, examination of women and children with voiding complaints have found that a substantial portion were victims of abuse or severe psychological trauma [6]. This association between abuse and urinary complaints has been attributed to an underlying psychological issue rather than a physiologic abnormality [16]. However, contemporary studies of the neurobiologic basis for stress and anxiety offer a plausible mechanism whereby physical or psychological abuse can sensitize micturition pathways, leading to an overactive bladder characterized by urinary urgency, usually with frequency or nocturia [17[en]19].…”
Section: Introductionmentioning
confidence: 99%